2020
DOI: 10.3389/fnins.2020.00384
|View full text |Cite
|
Sign up to set email alerts
|

Curdlan Prevents the Cognitive Deficits Induced by a High-Fat Diet in Mice via the Gut-Brain Axis

Abstract: A high-fat (HF) diet is a major predisposing factor of neuroinflammation and cognitive deficits. Recently, changes in the gut microbiota have been associated with neuroinflammation and cognitive impairment, through the gut-brain axis. Curdlan, a bacterial polysaccharide widely used as food additive, has the potential to alter the composition of the microbiota and improve the gut-brain axis. However, the effects of curdlan against HF diet-induced neuroinflammation and cognitive decline have not been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 79 publications
0
39
2
Order By: Relevance
“…The gut microbiome has emerged as a major contributor to cognitive health, and it can be remodeled by dietary factors. Recently, our laboratory demonstrated that gut microbiota dysfunction negatively impacts the cognitive impairments induced by HF diet [ 15 , 16 , 35 ]. Nevertheless, only a few studies focused on the alternation of gut microbiota occur before the onset of body weight gain in this model [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiome has emerged as a major contributor to cognitive health, and it can be remodeled by dietary factors. Recently, our laboratory demonstrated that gut microbiota dysfunction negatively impacts the cognitive impairments induced by HF diet [ 15 , 16 , 35 ]. Nevertheless, only a few studies focused on the alternation of gut microbiota occur before the onset of body weight gain in this model [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory demonstrated that gut microbiota dysfunction negatively impacts the cognitive impairments induced by HF diet [ 15 , 16 , 35 ]. Nevertheless, only a few studies focused on the alternation of gut microbiota occur before the onset of body weight gain in this model [ 35 ]. In previous long-term studies for HF diet for 8–22 weeks, it is reported that the proportion of gut bacteria belong to phylum Bacteroidetes is decreased, while phylum Firmicutes is increased in rodents with an increased ratio of Firmicutes to Bacteroidetes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…As metabolic substrates for beneficial bacteria, prebiotics have been shown to exert metabolic and cognitive benefits in association with compositional changes in the gut microbiota and their metabolites in the host. 5,[7][8][9][10][11][12][13][14] Human milk oligosaccharides (HMO) have been shown to have multi-functional, health-promoting activities and are consequently gaining considerable interest in the infant formula industry as well as for prebiotic applications in adults. 15 A handful of HMO are being produced industrially using recombinant methodology and supplementation of oligosaccharides such as 2′-fucosyllactose (2′-FL) and lacto-N-neotetraose (LNnT) to infant formula is now possible.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory demonstrated that gut microbiota dysfunction negatively impacts the cognitive impairments induced by HF diet [15,16,34]. Nevertheless, only a few studies focused on the alternation of gut microbiota occur before the onset of body weight gain in this model [34]. This study showed that the altered gut microbiota composition with a signi cant shift observed in the Firmicutes/Bacteroides ratio after acute HF diet feeding for 7 days.…”
Section: Discussionmentioning
confidence: 78%
“…There is accumulating evidence revealing that an HF diet for 8-22 weeks can alter the richness, diversity and composition of gut microbiota in obese mice [32,33], which is characterized by decreased Chao index and Shannon index, and increased representation of bacteria belonging to the Firmicutes phylum and decreased Bacteroidetes. Recently, our laboratory demonstrated that gut microbiota dysfunction negatively impacts the cognitive impairments induced by HF diet [15,16,34]. Nevertheless, only a few studies focused on the alternation of gut microbiota occur before the onset of body weight gain in this model [34].…”
Section: Discussionmentioning
confidence: 99%